Understanding the impact of drought in coffea genotypes - Fernandes, Isabel (2021)
Fellowships from CNPq, Brazil (F.L. Partelli and F.M. DaMatta), and FAPEMIG, Brazil (project CRA-RED-00053-16, to F.M. DaMatta) are also greatly acknowledged. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.